315 W, 1.94 μm, Tm:YAP InnoSlab laser. (1st February 2023) - Mao, Y F; Long, Q L; Gao, J M; Wang, Q C; Gao, Y; Wang, L
Abstract: In this letter, a high power, continuous-wave Tm:YAP InnoSlab laser has been developed. It produces 315 W of laser output power with an emission wavelength of 1.94 μ m. The optical-to-optical efficiency and slope efficiency with respect to the absorbed pump power are 53.4% and 63.8%, respectively. At the output power of 300 W, the beam quality factors M 2 are 201 in the x -direction and 3 in the y -direction, respectively. The beam shape is rectangular, thus it is ideal for pumping a Ho:YLF laser crystal in InnoSlab design for oscillator and amplifier.